Sensitivity of immune complex-dissociated p24 antigen testing for early detection of human immunodeficiency virus in infants. - Lewis, D E (1995)
Several investigators have suggested that early diagnosis of human immunodeficiency virus (HIV) infection in infants could be accomplished with a modified, more-sensitive, acid-dissociated p24 antigen enzyme-linked immunosorbent assay (ELISA) technique (p24 antigen immune complex dissociation [ICD]). We compared detection of HIV infection by HIV culture, PCR, and p24 antigen ICD assays in 46 infants by using samples collected independently. The detection sensitivity of the p24 antigen ICD assay was 0% with cord blood samples (2 HIV-positive infants), 38% with plasma samples from infants under 3 months of age (8 HIV-positive infants), and 58% overall (12 HIV-positive infants). By contrast, the sensitivities of HIV culture and PCR were 50% for cord blood samples, 75% for plasma samples from infants under 3 months of age, and 83% overall. These results indicate that the p24 antigen ICD does not offer the sensitivity necessary for this assay to be used as an indicator of HIV infection in infants.